Struktur Populasi dan Natural Increase Sapi Potong di Kecamatan Terbanggi Besar Kabupaten Lampung Tengah - A Oktafiana; Y Sukaryana; S S Kaffi (Politeknik Negeri Lampung, 2021)
This study aims to examine the population structure, natural increase and profile of beef cattle farms in Terbanggi Besar District, Central Lampung Regency. This research was conducted in the field through survey methods (simple random sampling and snowball sampling) in four villages in Terbanggi Besar District, Central Lampung Regency with descriptive analysis. The number of samples is 742 beef cattle from 95 cattle breeders, the respondents were selected to be interviewed by means of a questionnaire. The variables observed included population structure, birth rates, purchases and immigration, mortality rates, slaughter and sales rates, natural increases in cattle and the profile of beef cattle breeders. The results showed that the structure of the cattle population in Terbanggi Besar District, Central Lampung Regency, was based on the sex of 40.22% male and 59.78% female. The structure of the cattle population based on age is 64.51% adult cows, 22.67% young cows and 12.82% calves. The natural increase was 4.59% in population and 11.57% for adult females. The profile of beef cattle farms in Terbanggi Besar District is the 96.84% marriage system with Artificial Insemination, 90.53% intensive maintenance system, 90.53% feeding system and 87% health handling system with the help of animal health officers.